Respon Ganjar terhadap Protes Jadwal Kereta di Media Kompas.com, Analisis Wacana Kritis Norman Fairclough - Romadhon, Aris (Research Community for Critical Society and Environment, 2024)
Online news media such as Kompas.com, has become a dominant source of information for the public. In this context, news becomes one of the main forms of discourse that influences public opinion and views on important issues, public figures, and socio-political dynamics. In the context of language use, discourse analysis becomes an important tool to understand how mass media, especially online media, manipulates language and rhetoric to shape public perceptions and interpretations of various issues. Critical discourse analysis, as explained by Norman Fairclough, emerges as an approach that allows us to explore layers of hidden meaning in discourse, especially in the context of ideological practices. In this case, critical discourse analysis becomes relevant when applied to news involving public figures such as Ganjar Pranowo, a politician and governor of Central Java. Online media such as Kompas.com, as a very influential media, often present news about these figures with certain choices of words, framing, and language that can shape public perception. This study focuses on the critical discourse analysis of news about Ganjar Pranowo in one of the online media news Kompas.com has important value to fill this knowledge gap. Thus, this study will explain how critical discourse analysis can be used to analyze news about public figures, such as Ganjar Pranowo, published in the online media Kompas.com.